O-GlcNAc transferase acts as a critical nutritional node for the control of liver homeostasis - Paula Ortega-Prieto; Lucia Parlati; Fadila Benhamed; Marion Regnier; Isadora Cavalcante; Mélanie Montabord; Rachel Onifarasoaniaina; Maryline Favier; Natasa Pavlovic; Julie Magusto; Michèle Cauzac; Patrick Pagesy; et al. (JHEP Reports, 2024)
Background & Aims: O-GlcNAcylation is a reversible post-translational modification controlled by the activity of two enzymes, O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). In the liver, O-GlcNAcylation has emerged as an important regulatory mechanism underlying normal liver physiology and metabolic disease. Methods: To address whether OGT acts as a critical hepatic nutritional node, mice with a constitutive hepatocyte-specific deletion of OGT (OGTLKO) were generated and challenged with different carbohydrate- and lipid-containing diets. Results: Analyses of 4-week-old OGTLKO mice revealed significant oxidative and endoplasmic reticulum stress, and DNA damage, together with inflammation and fibrosis, in the liver. Susceptibility to oxidative and endoplasmic reticulum stress-induced apoptosis was also elevated in OGTLKO hepatocytes. Although OGT expression was partially recovered in the liver of 8-week-old OGTLKO mice, hepatic injury and fibrosis were not rescued but rather worsened with time. Interestingly, weaning of OGTLKO mice on a ketogenic diet (low carbohydrate, high fat) fully prevented the hepatic alterations induced by OGT deletion, indicating that reduced carbohydrate intake protects an OGT-deficient liver. Conclusions: These findings pinpoint OGT as a key mediator of hepatocyte homeostasis and survival upon carbohydrate intake and validate OGTLKO mice as a valuable model for assessing therapeutical approaches of advanced liver fibrosis. Impact and Implications: Our study shows that hepatocyte-specific deletion of O-GlcNAc transferase (OGT) leads to severe liver injury, reinforcing the importance of O-GlcNAcylation and OGT for hepatocyte homeostasis and survival. Our study also validates the Ogt liver-deficient mouse as a valuable model for the study of advanced liver fibrosis. Importantly, as the severe hepatic fibrosis of Ogt liver-deficient mice could be fully prevented upon feeding on a ketogenic diet (i.e. very-low-carbohydrate, high-fat diet) this work underlines the potential interest of nutritional intervention as antifibrogenic strategies.